Ultra-Sonographic Cut-off points of Cervical lymph nodes size and shape index in Hodgkin’s and Non-Hodgkin’s lymphoma - Ammar J. Sebahi; Fawaz Al-Aswad; Yasir H.Motlaq (Zien Journals, 2022)
Cervical lymph nodes (CLN) are frequently involved. there is no agreement on which cut-off point for lymph node size should be used in routine clinical practice to differentiate between cervical lymphadenopathy and normal CLN, that the optimal cut-off point of nodal size varies with the patient population. Aim of the study is to estimate Gray-scale Ultra-Sound (US) Cutoff Points of cervical lymph nodes (CLN) size and shape index of lymphomatous CLN of Hodgkinʼs lymphoma(HL), Non Hodgkinʼs lymphoma (NHL) groups in contrast to normal CLN in healthy Iraqi persons, and evaluate the difference among studied groups. This study involved 25 patients with HL, 25 with NHL (both with cervical lymphadenopathy) and 25 healthy subjects. all participants were examined using gray scale US machine. The results were : Means of long axis (L) and short axis (S) of NHL (21.47 mm, 13.23 mm ) and HL (23 mm, 13.59 mm) were significantly higher than healthy subjects (9.08 mm, 3.85 mm). Means of Short/Long axis ratio (S/L) were (0.634, 0.601, 0.424) mm respectively. Cutoff points for (L) of NHL, HL in contrast to control group were 13.85mm, while they were (5.800 and 7.150) mm for (S) and (0.540 and 0.447)mm for S/L respectively. Gray-scale US Cutoff Points of (L), (S) and S/L had strong diagnostic strength in differentiation between lymphomatous CLN and normal CLN in healthy subjects with no significant difference among diseased groups.
Keywords: Cervical lymph node; Gray-scale; Ultra-sound; Hodgkinʼs